Roman Lamps from Tilurium - Šimić-Kanaet, Zrinka (2012)
Roman legionary fortress Tilurium is located in the north-eastern part of the plateau above the right bank of the Cetina river (Hyppus) situated in Croatian south, Dalmatia. Systematic archeological excavations named ˝Project Roman military camps in Croatia - Tilurium begun by Department of Archeology at the Faculty of Philosophy, University of Zagreb with the assistance of the Ministry of Science, Education and Sports of the Republic of Croatia in 1997 and are still continued. A certain amount of archeological material found in the fortress Tilurium is made of Roman lamps. The typological analysis of the fragments asserted that the found artefacts belong to standard types of Firmalampen and Bildlampen lamps which were imported from Italy. The lamps can be dated from 1st to 5th century AD, which covers the time span from foundation of fortress to its downfall.